KARAKTERISTIK MORFOLOGI TANAH PADA SENTRA JAMBU METE DI KECAMATAN MAWASANGKA KABUPATEN BUTON TENGAH - IMBU, KAIMUDDIN; SYAF, HASBULLAH; ALAM, SYAMSU; HEMON, M TUFAILA; ZULFIKAR, ZULFIKAR; RUSTAM, LA ODE; HAKIM, DANI LUKMAN (Jurnal Agroteknos, 2024)
Morphological characteristics of the soil contribute to the development of agricultural commodities. This study aims to identify the morphological characteristics of soil in cashew land use in Banga Village, Mawasangka District, Central Buton Regency. This research was conducted by survey method and field analysis on cashew land use. morphological observations were made on five soil profiles of cashew land use. The results of the study showed that the characteristics of soil morphology in the cashew center in Mawasangka District generally have a few percentage of rock outcrops and surface rocks (120 cm); reddish brown and dark brown soil color; clay and clay loam texture; medium and fine granular structure with a weak degree of development; soil consistency in dry conditions is soft, moist conditions are very loose, and wet conditions with slightly sticky adhesion and plasticity are plastic. Such soil characteristic conditions affect the stem circumference and height of cashew plants. Based on the results of the study, it is suggested that there needs to be a direction for cashew commodity management in the form of pruning, thinning, or replacing new plants accompanied by fertilization based on the morphological characteristics of the soil formed to obtain optimal productivity